Clinical profile and skin prick test analysis in children with allergic rhinitis of North Kerala, India - K. P., Shyna; M., Veena Kumari; K., Divya Krishnan; V. K., Abdul Azeez (International Journal of Contemporary Pediatrics, 2018)
Background: Allergic rhinitis (AR) is increasing in prevalence among children globally and in India. Allergens are factors which trigger allergic rhinitis. Skin prick test (SPT) is a rapid, sensitive and cost effective test to detect IgE- mediated allergic diseases. Identification of common aeroallergens in an area is necessary, in order to educate the patient on what allergens to avoid and also help find the best formulation of allergen immunotherapy for effective AR treatment. This study was done to find the clinical profile and skin sensitivity to common allergens by skin prick test in children with allergic rhinitis between six and fifteen years. Methods: This cross-sectional study was conducted for a period of one year from January 2016 to December 2016. All children between 6 to 15 years with allergic rhinitis were included in the study. Skin prick test was done with seven most common allergens. Results: A total of 60 children with allergic rhinitis were studied and 42 patients (70%) tested positive for SPT. The major symptoms were persistent sneezing (68%), nasal itching (33%), rhinorrhea (85%) and nasal congestion (42%). The proportion of sneezers-runners was higher than blockers (64% versus 36). We tested seven common allergens and house dust mite allergen yielded the highest number of positive responses (33%) followed by cockroach (25%), alternaria (16.66%), parthenium (10%), cat dander (8.35%), sorghum (5%) and dog dander (5%). Among patients with SPT positivity; eight were positive to one allergen, thirteen were positive to two allergens, sixteen to three allergens and five to four allergens. Conclusions: Allergic Rhinitis with a number of allergic co morbidities has a significant impact on the quality of life and scholastic performance in children. Skin prick test which is a standardized, most rapid, sensitive and cost-effective test to detect IgE-mediated allergic diseases is helpful in identifying the common allergens. House dust mite is the commonest allergen tested positive in our study in children.